'It's almost like taking the sales out of selling'-Towards a conceptualization of value-based selling in business markets - Terho H; Haas A; Eggert A; Ulaga W (ELSEVIER SCIENCE INC, 2022)
While the creation of superior customer value is regarded as fundamental to a firm's long-term survival and growth, little is known about the effective implementation of a firm's value orientation at sales force level. As the sales force plays a pivotal role in implementing marketing strategies, this study adopts a discovery oriented approach and conceptualizes value-based selling as an effective sales approach in business markets. Based on in-depth interviews with sales managers in a variety of industries, we identify and portray three salient dimensions of value-based selling, namely (1) understanding the customer's business model, (2) crafting the value proposition, and (3) communicating customer value. The selling behavior entails a mutual orientation and focuses on the value-in-use potential of the offering for the customer's business profits. We argue that value-based selling is a unique concept that differs from the established selling approaches and propose a conceptual model linking value-based selling to performance outcomes. To further advance our knowledge about the effective implementation of a firm's value orientation, we identify future research avenues embracing qualitative and quantitative research methodologies. (C) 2011 Elsevier Inc. All rights reserved.